Peranan Keluarga Muslim dalam Pendidikan Karakter - Agus Kharir; Mucharror Mucharror (Maharot : Journal of Islamic Education, 2020)
The aim of this research is to describe the role of moslim’s family in character education. The implementation of the parenting club as an effort to support character education has been studied at two elementary level educational institutions, namely SD Lebah Putih or known as the School of Life Lebah Putih (SOL Lebah Putih) and also SD Islam Kurma Salatiga. In its implementation, this study uses a qualitative approach with type of research is a descriptive field research. There are three methods that researchers do in collecting data in the field, namely observation, Indeep interviews, and documentation. Whereas to find valid data sources, researchers use the snow ball method to fit the research objectives and the effectiveness of the data collected. After conducting field research, it was found that in these two basic education institutions prioritized the characteristics of authoritative parenting care. The school provides the basics of parenting and then the parents at home apply it according to the vis-missions agreed upon between parents and teachers. While the problem with the parenting program is more for parents, namely the lack of awareness of the main educational responsibilities. Because it is based on adult education, the school uses non-formal methods.